Efficient coverage greedy packet stateless routing in wireless sensor networks - Sivaram M.; Rohini R.; Rajanarayanan S.; Maseleno A.; Mohammed A.S.; Fareed Ibrahim B.; Goel P.M. (SAGE Publications Ltd, 2023)
Network routing; Packet networks; Power management (telecommunication); Extreme environment; Greedy perimeter stateless routing; Hybrid protocols; Periodic broadcasts; Positional information; Real-time application; Reduced power consumption; Stateless routing; Sensor nodes